2018
DOI: 10.1785/0120170258
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative View of the Microseismicity along the Western Main Marmara Fault

Abstract: A detailed study, based on ocean-bottom seismometers (OBSs) recordings from two recording periods (3.5 months in 2011 and 2 months in 2014) and on a high-resolution, 3D velocity model, is presented here, which provides an alternative view of the microseismicity along the submerged section of the North Anatolian fault (NAF) within the western Sea of Marmara (SoM). The nonlinear probabilistic software packages of NonLinLoc and NLDiffLoc were used for locating earthquakes. Only earthquakes that comply with the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…The seismicity patterns beneath both geodetic networks significantly differ but are consistent with the respective geodetic observations, where the fault segment with no seismicity seems locked, whereas the fault segment with a high level of seismicity is interpreted as being partially creeping. Although this observation is common for onshore faults, submarine faults may have a different behaviour due to the possible high amount of gas migrating upwards 42,44,45 and the large water content of the shallow sediments. The fault segment east of our geodetic network related to the Çınarcık Basin (CB) segment is characterized by seismicity which significantly increased 6 after the M w 7.4 1999 Izmit earthquake and was suggested to be related to stress increase imposed from the 1999 Izmit rupture zone to the eastern Sea of Marmara 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The seismicity patterns beneath both geodetic networks significantly differ but are consistent with the respective geodetic observations, where the fault segment with no seismicity seems locked, whereas the fault segment with a high level of seismicity is interpreted as being partially creeping. Although this observation is common for onshore faults, submarine faults may have a different behaviour due to the possible high amount of gas migrating upwards 42,44,45 and the large water content of the shallow sediments. The fault segment east of our geodetic network related to the Çınarcık Basin (CB) segment is characterized by seismicity which significantly increased 6 after the M w 7.4 1999 Izmit earthquake and was suggested to be related to stress increase imposed from the 1999 Izmit rupture zone to the eastern Sea of Marmara 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the events could be clearly identified on the seismograms allowing some earthquakes to be relocated (e.g. Batsi et al 2018). No particular site effect was noted, when comparing the amplitudes of a given earthquake on the network (Fig.…”
Section: Data Descriptionmentioning
confidence: 91%
“…They were deployed in the Central and Western parts of the SoM, mainly in and around the Tekirdag and Central basins as well as on the Western High (Figure 1). This zone is targeted due to its significant seismic activity [Tary et al, 2011;Schmittbuhl et al, 2016b;Batsi et al, 2018] and to its intense fluid manifestations including: i) the expulsion of gas bubbles in the water column [Géli et al, 2008;Dupré et al, 2015]; ii) the presence of gas and gas hydrates within the superficial sediments [e.g., Thomas et al, 2012]) along with the presence of mud accumulation and expulsion identified on the high-resolution bathymetry and seismic profiles [Grall et al, 2013] (Figure 2).…”
Section: Data and Networkmentioning
confidence: 99%
“…The cross-correlation is carried out solely for stations with time picks for the parent event. This could be complemented by additional picks using ray-tracing and an appropriate velocity model but we found that the calculated travel-times using the available 1-D velocity models [Tary et al, 2011;Géli et al, 2018] come with significant errors that might then prevent the phase identification for the newly detected events.…”
Section: Detection Algorithm and Relocation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation